IMPLEMENTASI QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK PENCEGAHAN KEGAGALAN PRODUKSI DRUM MINYAK PELUMAS di PT. X - Waluyo, Joko; Purwanto, Adi; S, Achmad Taufiq (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2004)
Quality Function Deployment is a process to translate the costumer needs into gathering of product specification, the technique or the way to choose combination of product attributes in direction to maximize costumer satisfaction will be finish with a method or an idea. The relationship between needs and size (volume) that guarantee all of costumer needs has been measure are made into the matrix. This matrix is the keywords that used on the house of quality. This research focused on Quality Function Deployment to search the failure cause that happened as the compentation between procees of production. Grouping failure choose the one that caused the biggest failure based on the research and then we try to solve the problem. The result of QFD and HOQ describes that priority based on the highest raw weight is theâ€ price attributeâ€ with nominal result 7.06, besides that the attribute of â€œimportance to costumerâ€ are on the deliver/dispatch precisely with nominal result 3.00. The highest â€œcostumer satisfactionâ€ attribute is on the paint guarantee with the nominal result 2.91. The company highest priority to realize is the paint guarantee with the sales point nominal 1.5, raw weight nominal 5.65, improvement ratio nominal 1.37, and costumer satisfaction nominal 2.91 with the goal nominal 4. On the second diagram, componen deployment matrix with the highest â€œdesign implementation weightâ€ are sorting the type of paint with nominal 880,08 and relative weight nominal 21,81%.